2016
DOI: 10.1371/journal.pone.0150609
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of an Atypical Hydrophobic Group 5 LEA Protein from Wild Peanut, Arachis diogoi Confers Abiotic Stress Tolerance in Tobacco

Abstract: Late embryogenesis abundant (LEA) proteins are a group of hydrophilic proteins, which accumulate in plants under varied stress conditions like drought, salinity, extreme temperatures and oxidative stress suggesting their role in the protection of plants against these stresses. A transcript derived fragment (TDF) corresponding to LEA gene, which got differentially expressed in wild peanut, Arachis diogoi against the late leaf spot pathogen, Phaeoisariopsis personata was used in this study. We have cloned its fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 96 publications
2
27
0
Order By: Relevance
“…grandis defense against stressful conditions. The late embryogenesis abundant protein encoding gene LEA has been widely reported to participate in responses to drought, cold, and salt stresses, and ABA treatment, and plays an important role in plant tolerance to abiotic stress [4751]. The significantly increased expression of SgLEA under drought, cold, salt, high pH and ABA treatments (Fig 5A–5E) implies that SgLEA participates in S .…”
Section: Discussionmentioning
confidence: 99%
“…grandis defense against stressful conditions. The late embryogenesis abundant protein encoding gene LEA has been widely reported to participate in responses to drought, cold, and salt stresses, and ABA treatment, and plays an important role in plant tolerance to abiotic stress [4751]. The significantly increased expression of SgLEA under drought, cold, salt, high pH and ABA treatments (Fig 5A–5E) implies that SgLEA participates in S .…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis of 5C LEA proteins showed that the molecular mechanisms of the protective ability against desiccation stress were diverse. The overexpression of AdLEA, a 5C LEA protein from wild peanut, could help maintain the photosynthetic efficiency, reduce the ROS level, and induce the expression of some drought-responsive genes in transgenic tobacco [26]. Meanwhile, overexpressing SiLEA14 from foxtail millet enhanced a higher level of proline and sugar accumulation in transgenic Arabidopsis [13].…”
Section: Discussionmentioning
confidence: 99%
“…A small number of group 5C LEA proteins have been characterized, but their physical characteristics and biological functions are largely unknown. Some members of group 5C were identified in other plants such as cotton LEA14A, soybean D95-4, tomato ER5, hot pepper CaLEA6, Arabidopsis AtLEA14A, sweet potato IbLEA14A, rice OSLEA5, foxtail millet SiLEA14A, and wild peanut LEA [8,13,[20][21][22][23][24][25][26]. The expression of LEA 5C proteins is upregulated by ABA and multiple abiotic stresses including salt and drought [13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Despite of many research efforts to gain a better understanding of the mechanisms adopted by plants to cope or avoid salt stress, mechanisms of salt tolerance in plants, especially at genetic level are not yet fully understood. However, several studies have indicated that salt stress induces the expression of many specific metabolites and their modifications . Therefore, in this review article, we have presented certain representative classes of metabolites, their genetic basis, and the underlying genes that control these metabolites which ultimately help plants to survive during the salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have indicated that salt stress induces the expression of many specific metabolites and their modifications. [10][11][12][13] Therefore, in this review article, we have presented certain representative classes of metabolites, their genetic basis, and the underlying genes that control these metabolites which ultimately help plants to survive during the salt stress. Furthermore, by combining all the available literature the deficiencies in the current research are highlighted along with the postulation of a stronger and successful integrated approach for crop plants to combat salt stress.…”
Section: Introductionmentioning
confidence: 99%